History and Super Diversity - Kate Hawkey (MDPI AG, 2012)
The article looks at the perspectives on history amongst adolescent children of different backgrounds living in inner-cities in England and builds on previous research in this area. The current article presents exploratory research which focuses on the views of particular groups of adolescents, namely those from long established settled immigrant communities; those from more recently arrived migrant and immigrant communities; and those from white indigenous communities. An inclusive, perspectival and dynamic approach towards history education is outlined and the underlying view of knowledge and implications for pedagogy of this approach discussed alongside comparisons with other approaches towards the subject. The exploratory work and analysis is used to generate a research agenda through which history for a super diverse society can be developed. Although the research was conducted in the English context, the issues it raises are pertinent elsewhere.